Mechanical Performance and Stress Redistribution Mechanisms in Photovoltaic Support Connections: A Finite-Element-Driven Design Optimization Study - Deli Zhang; Ruwei Wang; Juan Liu; Xuanming Huang (Applied Sciences)
The photovoltaic industry plays a critical role in promoting global sustainability. Enhancing the reliability of photovoltaic structures is essential for achieving sustainable development. This study involved the analysis of a photovoltaic power generation project in Hubei Province to compare differences in the structural loads of photovoltaic supports as outlined in Chinese, American, and European codes. Additionally, the ABAQUS numerical simulation was used to investigate the mechanical characteristics of photovoltaic support joint connections and analyze the causes of structural deformation. Innovative joint connections were proposed to optimize the structural performance of photovoltaic supports. The results showed that photovoltaic supports designed using Chinese codes exhibit lower reliability compared to those designed using American and European codes. Specifically, at least three bolts should be installed at the purlin hanger to connect the purlin and the beam. Z-shaped and Π-shaped purlin hangers are recommended for connecting beams and purlins, as they reduce joint deformation while preventing excessive stress in L-shaped purlin hangers. C-shaped steel is suggested for braces, offering both ease of construction and structural reliability. The proposed connection design minimizes additional steel consumption while enhancing overall performance.